Salty Food Consumption and Its Association with Chronic Kidney Disease Among Older Adults in Indonesia: Findings from the 2023 National Health Survey - Heny Nurmayunita; Amin Zakaria; Ananda Sagita Maharani; Yuni Asri; Ninik Murtiyani (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Chronic kidney disease (CKD) is an escalating public health issue, particularly among the elderly. High salt intake is a modifiable dietary risk factor suspected to accelerate CKD progression. However, large-scale evidence from Indonesia remains scarce. This study investigates the association between salty food consumption and CKD among older adults in Indonesia. Using data from the 2023 Indonesia Health Survey (Survei Kesehatan Indonesia/SKI 2023), we analyzed 97,339 individuals aged 60 and above. Descriptive statistics outlined participant characteristics, while chi-square tests and binary logistic regression assessed associations and adjusted effects. Statistical analyses were conducted using STATA 14.1, with significance set at p < 0.05. Among participants, 89.3% reported consuming salty foods, and CKD prevalence was 0.5%. Bivariate analysis showed significant associations between CKD and sex, education, and salty food intake (p < 0.001). Multivariate results indicated that elderly individuals who did not consume salty food had significantly reduced odds of CKD (OR = 0.70; 95% CI: 0.54–0.90; p = 0.006), suggesting a protective effect. These findings highlight a strong association between salty food consumption and CKD risk in Indonesia’s aging population. Reducing dietary salt intake may serve as an effective, low-cost intervention for CKD prevention. Urgent public health strategies focusing on dietary behavior change and nutrition education for the elderly are needed to curb the rising burden of kidney disease.